Implementasi Program Indonesia Coral Reef Garden Bali (ICRG BALI) - Gultom, Iqbal Suhaemi; Anggoro , T. Danny; Nugraha , R. Bambang Adhitya (Jurnal Ilmiah Administrasi Publik, 2022)
Bali island is one of the international tourism destinations providing the main income from the tourism sector. Pandemic COVID-19 has caused economic disruption to the people in Bali due to travel restrictions so that travelers can not make visits to Bali. The government of Indonesia has attempted to overcome economic disruption caused by pandemic COVID-19 in Bali by launching the National Economic Recovery (PEN) program in the form of coral garden development or what is known as Indonesia Coral Reef Garden (ICRG) Bali. This program is implemented through a labor-intensive scheme that aims to provide an economic stimulant as well as efforts to restore the coral reefs. Based on the analysis, it is obtained lesson learned that economic stimulants can reach more target groups and restoration requires monitoring and maintenance efforts.